Tata Kelola Teknologi Informasi dalam Transformasi Digital Nasional Indonesia: Tinjauan Literatur Sistematis - Rachelina Putri Arta Saragih; Jonathan Arya Wibowo; Alfiya Zain Saputri (Informatics Department, Faculty of Mathematics and Natural Sciences, Udayana University, 2026)
Digital transformation is Indonesia's principal national development strategy, pursued through the Making Indonesia 4.0 roadmap (2018) and the Indonesia Digital Roadmap 2021–2024. IT governance nevertheless confronts policy fragmentation, cyber vulnerability, and access disparities that threaten Indonesia's ambition of becoming one of the world's ten largest digital economies by 2030. This study conducts a systematic literature review following PRISMA 2020 guidelines, screening 1,248 initial articles in stages, narrowing to 456 after title and abstract screening and finally to 20 articles after full-text review, drawn from six major databases covering 2021–2025. The process identified five COBIT 2019 domains, with risk management (15 of 20 articles; 75%) and strategic alignment (14 of 20 articles; 68%) as the highest priorities, while performance measurement remained the weakest dimension. Thematic analysis using NVivo 14 yielded 22 major themes and informed the Indonesian IT Governance Index (IITGI), an initial score of 0.68 combining 38 OECD Digital Government Index indicators with 10 Indonesia-specific contextual indicators covering disaster resilience and sharia-economy inclusiveness. Indonesia falls outside the coverage of the OECD Digital Government Index and cannot be benchmarked directly against member countries; this limitation is itself part of the rationale for developing the IITGI. The findings recommend establishing a National IT Governance Council, a civilian national cyber security coordination body, and a real-time performance dashboard. The theoretical contribution lies in mapping the five COBIT domains and the resulting IITGI score onto Fountain's Technology Enactment Framework, grounding the framework's adaptation in empirical findings. This is translated into a 2026–2028 roadmap for the Ministry of Communication and Digital Affairs aimed at inclusive and sustainable digital transformation.